The number and phenotype of myocardial and adipose tissue CD68+ cells is associated with cardiovascular and metabolic disease in heart surgery patients - Pierzynová, Aneta; Šrámek, Jaromír; Cinkajzlová, Anna; Kratochvílová, Helena; Lindner, Jaroslav; Haluzík, Martin; Kučera, Tomáš (Nutrition, metabolism, and cardiovascular diseases, 2019)
BACKGROUND AND AIMS: CD68+ cells are a potent source of inflammatory cytokines in adipose tissue and myocardium. The development of low-grade inflammation in adipose tissue is implicated in the pathogenesis of obesity-associated disorders including type 2 diabetes mellitus (T2DM) and cardiovascular disease. The main aim of the study was to characterize and quantify myocardial and adipose tissue CD68+ cells and adipose tissue crown-like structures (CLS) in patients with obesity, coronary artery disease (CAD) and T2DM. METHODS AND RESULTS: Samples were obtained from the right atrium, epicardial (EAT) and subcutaneous adipose tissue (SAT) during elective heart surgery (non-obese, n = 34 patients; obese, n = 24 patients). Immunohistochemistry was used to visualize CD68+ cells. M1-polarized macrophages were visualized by immunohistochemical detection of CD11c. The proportion of CD68+ cells was higher in EAT than in SAT (43.4 ± 25.0 versus 32.5 ± 23.1 cells per 1 mm2; p = 0.015). Myocardial CD68+ cells were more abundant in obese patients (45.6 ± 24.5 versus 27.7 ± 14.8 cells per 1 mm2; p = 0.045). In SAT, CD68+ cells were more frequent in CAD patients (37.3 ± 23.0 versus 23.1 ± 20.9 cells per 1 mm2; p = 0.012). Patients having CLS in their SAT had higher average BMI (34.1 ± 6.4 versus 29.0 ± 4.5; p = 0.024). CONCLUSIONS: Regional-based increases in the frequency of CD68+ cells and changes of their phenotype in CLS were detected in obese patients and CAD patients. Therapeutic modulation of adipose tissue inflammation may represent a target for treatment of obesity.
Keywords: biologické markery; Antigens, CD; lidé; Middle Aged; Adult; Case-Control Studies; Obesity; nemoci koronárních tepen; makrofágy; antigeny CD11c; fenotyp; Female; Crown-like structures; Epicardium; počet buněk; Phenotype; Humans; Inflammation; podkožní tuk; Coronary Artery Disease; myokard; studie případů a kontrol; obezita; Cell Count; zánět; Subcutaneous Fat; lidé středního věku; Biomarkers; diabetes mellitus 2. typu; mužské pohlaví; CD11c Antigen; Diabetes Mellitus, Type 2; Antigens, Differentiation, Myelomonocytic; antigeny diferenciační myelomonocytární; ženské pohlaví; Myocardium; Type 2 diabetes mellitus; Aged, 80 and over; senioři nad 80 let; Male; Aged; Coronary artery disease; dospělí; Macrophages; CD antigeny; senioři